2021
DOI: 10.1136/annrheumdis-2021-220884
|View full text |Cite
|
Sign up to set email alerts
|

EULAR points to consider for conducting clinical trials and observational studies in individuals at risk of rheumatoid arthritis

Abstract: BackgroundDespite growing interest, there is no guidance or consensus on how to conduct clinical trials and observational studies in populations at risk of rheumatoid arthritis (RA).MethodsAn European League Against Rheumatism (EULAR) task force formulated four research questions to be addressed by systematic literature review (SLR). The SLR results informed consensus statements. One overarching principle, 10 points to consider (PTC) and a research agenda were proposed. Task force members rated their level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 128 publications
0
42
0
Order By: Relevance
“…Third, the participants included within our review were either individuals with musculoskeletal symptoms but without clinical arthritis or FDRs of individuals with RA recruited through secondary care; therefore, our findings provide limited insights into the perceptions and experiences of other individuals at-risk of developing the condition, such as other asymptomatic at-risk individuals (eg, indigenous North Americans who are at increased genetic risk) and at-risk individuals with early clinical arthritis, including patients with palindromic rheumatism and undifferentiated arthritis. 18 We acknowledge that the themes we have identified might potentially differ between the different groups of individuals at-risk included within this review (eg, in terms of their knowledge of RA), as well as groups of at-risk individuals not represented in study samples. Additionally, while our search strategy included the term ‘inflammatory arthritis’, no qualitative studies relating to patients at-risk of inflammatory arthritides other than RA were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the participants included within our review were either individuals with musculoskeletal symptoms but without clinical arthritis or FDRs of individuals with RA recruited through secondary care; therefore, our findings provide limited insights into the perceptions and experiences of other individuals at-risk of developing the condition, such as other asymptomatic at-risk individuals (eg, indigenous North Americans who are at increased genetic risk) and at-risk individuals with early clinical arthritis, including patients with palindromic rheumatism and undifferentiated arthritis. 18 We acknowledge that the themes we have identified might potentially differ between the different groups of individuals at-risk included within this review (eg, in terms of their knowledge of RA), as well as groups of at-risk individuals not represented in study samples. Additionally, while our search strategy included the term ‘inflammatory arthritis’, no qualitative studies relating to patients at-risk of inflammatory arthritides other than RA were found.…”
Section: Discussionmentioning
confidence: 99%
“…At-risk populations eligible for inclusion were (1) asymptomatic at-risk individuals, which includes first-degree relatives (FDRs) of people with RA and indigenous North Americans; (2) at-risk individuals with musculoskeletal symptoms without clinical arthritis; and (3) at-risk individuals with early clinical arthritis, which includes patients with palindromic rheumatism and undifferentiated arthritis. 18 We included full articles in the English language that were published in peer-reviewed journals. Conference abstracts were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Only recently, the European Alliance of Rheumatology (EULAR) has published points to consider for conducting clinical trials and observational studies in at-risk individuals ( 46 ). The different outcomes for assessment agreed on within our consortium are also named in this recommendation paper, which also reflects the different phases in the development of arthritis, and the foci that are set in the contributing individual registries.…”
Section: Discussionmentioning
confidence: 99%
“…These are individuals without a diagnosis of RA who have either (i) genetic risk factors for RA, (ii) environmental risk factors for RA, (iii) systemic autoimmunity associated with RA, (iv) symptoms without clinical arthritis or (v) unclassified arthritis [ 7 ]. Core risk factors for RA have now been defined [ 8 ], and EULAR guidelines for conducting clinical trials and observational studies in individuals at risk of rheumatoid arthritis have been published [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the increasing focus on prevention of RA [ 8 , 9 ], the present systematic review of studies to elicit preferences for RA treatments updates and extends the previous review [ 6 ] by including studies of the preferences of individuals who do not have RA, and those of ‘at risk’ populations for RA prevention [ 17 ]. This inquiry will explore differences between preference studies for RA treatment and prevention, and across different populations (patients, general public, at risk groups).…”
Section: Introductionmentioning
confidence: 99%